2021
DOI: 10.1186/s12888-021-03443-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of high sensitive C-reactive protein and IL − 6 markers in patients with treatment-resistant schizophrenia in Ethiopia: a comparative study

Abstract: Background Accumulating evidence indicates that schizophrenia is accompanied by significant activation of the immune system; however, there is limited data from low and middle-income countries (LMIC). Inflammatory markers may be more relevant in LMIC settings where infectious conditions are more prevalent and may thus play some role in the causation and maintenance of schizophrenia. The aim of this study was to assess the level of inflammatory markers high sensitive C-reactive protein (hsCRP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…In 1998, Lin et al found that serum IL-6 levels in TRS were significantly higher than in healthy controls [ 4 ]. This finding was also supported by subsequent studies [ 8 , 17 21 ]. While the differences in IL-6 levels between TRS and treatment-responsive schizophrenia were not significant in some of these studies [ 4 , 8 ].…”
Section: Introductionsupporting
confidence: 88%
“…In 1998, Lin et al found that serum IL-6 levels in TRS were significantly higher than in healthy controls [ 4 ]. This finding was also supported by subsequent studies [ 8 , 17 21 ]. While the differences in IL-6 levels between TRS and treatment-responsive schizophrenia were not significant in some of these studies [ 4 , 8 ].…”
Section: Introductionsupporting
confidence: 88%
“…In 1998, Lin et al found that serum IL-6 levels in TRS were significantly higher than in healthy controls [4]. This finding was also supported by subsequent studies [8,[17][18][19][20][21]. While the differences in IL-6 levels between TRS and treatment-responsive schizophrenia were not significant in some of these studies [4,8].…”
Section: Introductionmentioning
confidence: 83%
“…23 Patients with history of schizophrenia or depression were also excluded, as the standard therapy for these psychological disorders may also change serum biomarker levels. 24,25 In addition to TPE, the last decade has seen the development of early intervention in specialized ICU, rituximab therapy, N-acetylcysteine, and more recently, Caplacizumab, which lead to great improvements in the prognosis of patients with TTP. 2,[26][27][28] Except for Caplacizumab, which was not approved by SFDA, all subjects in our study received standard care for TTP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we excluded those with severe hepatic or renal dysfunction, which may impact the level of serum biomarkers 23 . Patients with history of schizophrenia or depression were also excluded, as the standard therapy for these psychological disorders may also change serum biomarker levels 24,25 . In addition to TPE, the last decade has seen the development of early intervention in specialized ICU, rituximab therapy, N‐acetylcysteine, and more recently, Caplacizumab, which lead to great improvements in the prognosis of patients with TTP 2,26–28 .…”
Section: Discussionmentioning
confidence: 99%